Public and private in italian health care: trends and market quotas (Italian Journal of Public Health, 2006)
Background: The Italian healthcare system has two components: public and private healthcare providers.Both deliver services on behalf of and payable by the national health care service. This study explores therelationships between public and private healthcare providers.Methods: The number of hospital admissions and length of stay or number of times the service was accessedstratified by year 2000, 2001, 2002; DRG; type of hospital admission (ordinary or day hospital/surgery); healthprovider category: public institutions without a specific reference territory, public institutions with a specificreference territory and accredited private institutions and medical or surgery DRGs. A distinction is madebetween those DRGs defined as belonging to the private sector and those falling within the public sector,assuming there is a majority market portion for services primarily supplied by the private sector. Case-mixindex was utelised as the indicator for the complexity of the cases treated and the comparative performanceindex was used as the indicator for efficiency. Lastly in order to evaluate the services delivered with aninappropriate organizational profile reference is made the rulings defining Essential Level of assistance.Results: The results showed a shift in the reallocation of service volumes for ordinary admissions towardsthe private sector; the reallocation relates to the volumes but not to the types of cases treated, since the DRGmix remained substantially unchanged over the 3-year period and those DRG that absorb 51% of serviceswere essentially constant. The private sector never achieved a market majority quota but rather controlledmarket niches with minority quotas. The private institutions treated less complex cases and worked withlower efficiency levels than the public sector. There was also a shift in the distribution of admissions fromordinary admissions to day hospital/day surgery regimes with a growth in the proportion of the latter.Conclusions: The study confirmed the predominance of public healthcare providers in the Italian healthcaresystem as well as their higher complexity and efficiency levels.
Keywords: public and private healthcare providers; managed competition; market quotas,; DRG; italian health care